High Resolution Microsatellite Marker Analysis of Some Rice Landraces Using Metaphor Agarose Gel Electrophoresis - K. Kristamtini; T. Taryono; Panjisakti Basunanda; Rudi Hari Murti (Indonesian Journal of Biotechnology, 2015)
Microsatellite markers or simple sequences repeats are DNA - based molecular techniques that areused to see the different among accessions and inbred lines. There are three methods to analysis the results ofthe polymerase chain reaction of microsatellite markers namely polyacrylamide gel electrophoresis (PAGE),capillary electroforesis, and Metaphor Agarose Gel Electroforesis (MAGE), and the Use of MAGE assessedmore easily and economically the polymorphic pattern of DNA markers. This study aimed to obtain fast,effective and efficient in term of easy and cheap technique to identify microsatellite markers of some blackrice cultivars and F2 populations from crosses between black with white rice. The results showed that MAGEsuccessfully separated clearly SSRs alleles with different sizes of less than 25 bp .